PENGARUH KEADILAN ORGANISASIONAL TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KOMITMEN DAN INTENSI KELUAR - JOHN GUSTINUS LEONARDO (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2019)
The purpose of this research is to find the influence of organizational justice TO job satisfaction and its impact to the commitments organizations and turnover employees at PT Waskita Karya Pusat dan Cabang Banten. Respondents in this research was permanent workers as many as 234 employees. Technique the sample collection uses proportional random sampling. Technique analysis in this research using analysis structural equation modeling-partial least square (SEM-PLS with software SmartPLS 2.00 version). The research results show that organizational justice positively and significant to depend on the work satisfaction. This means that the better the level of justice organizational, so the higher an employee will job satisfaction. Organizational Justice positively and significant to organization commitment. This means that the better organizational justice, then it would be more many employees behave organization commitment. Organisational justice in a negative impact to intent turnover of employees. This means that the better justice organizational, so the level of intent turnover employees will be down. Satisfaction of a work as positive to depend on the organisational commitment. This means that the higher the level of job satisfaction, organisational employees will to step up their commitment. Job satisfaction is employee turnover intent negative impact. This means that the higher the level of work satisfaction the more one is low out employee’s intent.